2017
DOI: 10.1021/acs.jpclett.7b02138
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Driven Resistive Switching in Solution-Processable Thin Films of Coordination Polymers

Abstract: Metal−organic coordination polymers (CPs) downsized to thin films with controllable electrical conductivity are promising for electronic device applications. Here we demonstrate, for the first time, thermally driven resistive switching in thin films of semiconducting CPs consisting of silver ion and tetracyanoquinodimethane ligand (AgTCNQ). High-quality and highly hydrophobic thin films of Ag-TCNQ were fabricated through a layer-by-layer approach upon sacrificing a pre-deposited layer of Cu-TCNQ on a thiolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 45 publications
8
40
0
Order By: Relevance
“…Upon dosing I 2 vapor with a Cu-TCNQ thin film device, an unusual rectification in the electrical conductance was observed, which can be attributed to the formation of a Cu-I/Cu-TCNQ heterostructure, an interesting effect of chemical reaction at the solid–gas interface involving CP (Figure c). It is worthwhile to mention that our Cu-TCNQ (also Ag-TCNQ) thin film is prone to exhibit thermally driven resistive switching (10 7 Ω at 300 K ↔ 10 Ω 400 K), which is an interfacial phenomenon unlike earlier reports on chemically driven and/or structurally driven resistive switching in thin films of Cu-TCNQ …”
Section: Interfacial Reduction Reactionmentioning
confidence: 70%
See 1 more Smart Citation
“…Upon dosing I 2 vapor with a Cu-TCNQ thin film device, an unusual rectification in the electrical conductance was observed, which can be attributed to the formation of a Cu-I/Cu-TCNQ heterostructure, an interesting effect of chemical reaction at the solid–gas interface involving CP (Figure c). It is worthwhile to mention that our Cu-TCNQ (also Ag-TCNQ) thin film is prone to exhibit thermally driven resistive switching (10 7 Ω at 300 K ↔ 10 Ω 400 K), which is an interfacial phenomenon unlike earlier reports on chemically driven and/or structurally driven resistive switching in thin films of Cu-TCNQ …”
Section: Interfacial Reduction Reactionmentioning
confidence: 70%
“…Thus, we observed a spontaneous reduction of Cu­(II) to Cu­(I) at the solid–liquid interface, also known as IRR. Notably, in the liquid- phase (i) no reduction of Cu­(II) to Cu­(I) vis-à-vis the formation of Cu-TCNQ took place upon mixing ethanolic Cu­(OAc) 2 and TCNQ solutions and (ii) Cu­(I)-TCNQ was precipitated out upon mixing CuI and TCNQ solutions almost instantaneously …”
Section: Interfacial Reduction Reactionmentioning
confidence: 99%
“…S16 †). 32,53 The Raman band of pristine Cu-TCNQ at 520 cm À1 (perhaps due to the Cu/Cu interaction mode) was absent in our doped thin lm (Fig. S17 †).…”
Section: Resultsmentioning
confidence: 95%
“…Electrical transport measurements (I-V) on various thin lm samples were carried out using a Keithley 4200 SCS Parameter Analyser system attached to an Everbeing probe station (equipped with a thermal chuck) with a eutectic gallium indium (EGaIn) alloy as the top electrode. 53…”
Section: Characterizationmentioning
confidence: 99%
“…chemical sensors, and energy storage [89][90][91][92]. Moreover, in the process of continuous research, MOFs have been reported as promising candidates for flexible resistive switching and memristor applications [28,46,[93][94][95][96][97][98][99][100].…”
Section: Reviewsmentioning
confidence: 99%